Fibroblast Growth Factor 8 Expression in GT1-7 GnRH-Secreting Neurons Is Androgen-Independent, but Can Be Upregulated by the Inhibition of DNA Methyltransferases - Linscott, Megan L.; Chung, Wilson C. J. (Frontiers in Cell and Developmental Biology, 2016)
Fibroblast growth factor 8 (FGF8) is a potent morphogen that regulates the embryonic development of hypothalamic neuroendocrine cells. Indeed, using Fgf8 hypomorphic mice, we showed that reduced Fgf8 mRNA expression completely eliminated the presence of gonadotropin-releasing hormone (GnRH) neurons. These findings suggest that FGF8 signaling is required during the embryonic development of mouse GnRH neurons. Additionally, in situ hybridization studies showed that the embryonic primordial birth place of GnRH neurons, the olfactory placode, is highly enriched for Fgf8 mRNA expression. Taken together these data underscore the importance of FGF8 signaling for GnRH emergence. However, an important question remains unanswered: How is Fgf8 gene expression regulated in the developing embryonic mouse brain? One major candidate is the androgen receptor (AR), which has been shown to upregulate Fgf8 mRNA in 60-70% of newly diagnosed prostate cancers. Therefore, we hypothesized that ARs may be involved in the regulation of Fgf8 transcription in the developing mouse brain. To test this hypothesis, we used chromatin-immunoprecipitation (ChIP) assays to elucidate whether ARs interact with the 5’UTR region upstream of the translational start site of the Fgf8 gene in immortalized mouse GnRH neurons (GT1-7) and nasal explants. Our data showed that while AR interacts with the Fgf8 promoter region, this interaction was androgen-independent, and that androgen treatment did not affect Fgf8 mRNA levels, indicating that androgen signaling does not induce Fgf8 transcription. In contrast, inhibition of DNA methyltransferases (DNMT) significantly upregulated Fgf8 mRNA levels indicating that Fgf8 transcriptional activity may be dependent on DNA methylation status.